Analysis of Barriers to Inclusive Schools in Germany: Why Special Education Is Necessary and Not Evil - Bernd Ahrbeck; Marion Felder (MDPI AG, 2020)
Over the past decade, ever since the ratification of the United Nations Convention on the Rights of People with Disabilities (UN-CRPD) in Germany, a morally charged debate has taken place about inclusive and special education. Special schools are under considerable attack and even special education is deemed responsible for the difficulties in implementing full inclusion in schools. The gravest accusation is that special education and special schools are even today a close connection to the Nazi era between 1933 and 1945, when children with disabilities were sterilized and murdered. Special education is seen as a symbol and guarantor of separation and exclusion and therefore incompatible with the idea of inclusion. This article will outline and analyze this claim and present other more compelling reasons why full inclusion has been difficult to implement in Germany. Following the analysis, we will describe a possible way forward for inclusion and special education.